A follow-up study of the relationship between maternal phubbing and hyperactivity tendency among children - Liu Xingjuan; Sui Yang (ITM Web of Conferences)
This follow-up study investigated 896 subjects twice (9 months in between) from one middle school and one primary school in Guangdong province to explore the developments of maternal phubbing and hyperactivity tendency among children, as long as the causal effect between maternal phubbing and hyperactivity tendency among children. The results indicated as follows: maternal phubbing was significantly correlated to hyperactivity tendency among children, which indicated that maternal phubbing is one of the risk factor causing hyperactivity tendency among children．